The West's darling in Syria: Seeking support, the Kurdish Democratic Union Party brandishes an anti-jihadist image - Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2015)
US bombings in 2015 repulsed Islamic State attacks on cities in mostly Kurdish self-rule regions called cantons in northern Syria. The three cantons, which border Turkey, are dominated by the Kurdish Democratic Union Party (PYD). The party is linked to the Kurdistan Workers' Party (PKK), a former client of the Syrian regime and considered a "terrorist" group by the United States, the European Union, and Turkey. At the risk of deepening an Arab Sunni backlash that has fanned radicalization, Washington is set ever more on the prospect of the PYD retaking mostly Arab territory captured by the Islamic State. In line with German reluctance to arm warring sides, Berlin has refrained from giving military aid to the PYD, which is accused of carrying out war crimes. Still, an international effort to rebuild the cantons tied to breaking the PYD's monopoly on them could help stabilize the area - even more so if Turkey could be brought on board. (SWP Comments)
Keywords: 320